Reporting comprehensive income and firms' earnings management - Wei, Zhang (Journal of Accounting, Business and Finance Research, 2023)
This study investigates the impact of reporting comprehensive income and other income through performance or equity statements on firms' earnings management through the selective sale of available-for-sale (AFS) securities. The objective is to explore how Canadian firms can improve transparency by altering managers' accounting behavior by switching from equity statements to income statements. The study used a difference-in-differences method in a quasi-experimental framework. The results showed that negative net income and post-period net income in performance statements can reduce realized gains and losses. Available-for-sale securities also affect these gains and losses in performance and equity statements. Single statement adopters only smooth earnings when net income is positive or when available-for-sale gains are large enough to offset negative earnings. Income statement (IS) adopters reduced earnings smoothing more than other treatment firms. Managers with less job security were found to be more likely to engage in earnings smoothing, and earnings smoothing decreased more during the pre-to-post period. Equity incentives reduced the tendency to smooth earnings, particularly in treatment firms with CEOs whose pay is more sensitive to stock price changes. Treatment firms outperform control firms in predicting future earnings using realized gains and losses on AFS securities per share. The findings suggest that firms manage earnings less effectively by selectively selling AFS securities when comprehensive income (CI) or other comprehensive income (OCI) is presented in performance statements. Firms win when earnings management is reduced because it reduces the informativeness of realized gains and losses on AFS securities. Managers will use more earnings management strategies as long as they have incentives.